Mobilising the Next Generation of Planetary Health Leaders: The Dynamism of Youth Engagement in Malaysia - Saidatul, Maisarah Faiesall *; Sarah, Hanani Ahmad Tajuddin; George, Andrew Jason *; Nur Hazirah, Marzuki *; Lacey-Hall, Oliver; Jemilah, Mahmood *; Clements, Gopalasamy Reuben *; Guinto, Renzo R * (MDPI, 2023)
With planetary health gaining traction as a global movement and problem-solving approach, this trans-disciplinary field is well-placed to provide an exciting and dynamic platform to promote engagement with young people. Previous studies have shown that although there is great energy and passion from youth, the global planetary health community struggles in sustaining young people’s motivations and engagement in today’s crowded physical and online environments. Planetary health advocates are also dealing with an increase in climate anxiety that has taken a toll on the emotional and mental wellbeing of young people. Here, we review our experience in engaging youth groups and networks in Malaysia through a four-pronged approach (consultation, facilitation, capacity-sharing, and evidence-building), as well as challenges commonly faced by the planetary health community in educating and building a youth movement. After a year of engagement, we found that mobilising the next generation of planetary health leaders requires a change in existing power dynamics to a capacity-sharing model, an emphasis on clear, simplified, and effective communications that utilise the mainstream youth spaces (e.g., social media), and hopeful messages to counter apathy and anxiety into action.